EFEKTIVITAS MODEL PEMBELAJARAN WORD SQUARE DALAM MENINGKATKAN KEMAMPUAN KOSAKATA BAHASA INDONESIA PESERTA DIDIK KELAS III SEKOLAH DASAR - Karina Rita Yanisa; Siska Mega Diana; Siti Nuraini; Erni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low Indonesian vocabulary ability of third-grade elementary school students. The purpose of this study is to determine the effectiveness of the word square learning model on the Indonesian vocabulary ability of third-grade elementary school students at MIN 2 Metro Pusat. This research method is a quasi-experimental research with a non-equivalent control group design. The population in this study were all third-grade elementary school students at MIN 2 Metro Pusat totaling 110 students and the sample determination used a simple random sampling technique with a total of 52 students. Data collection techniques used test and non-test techniques. Data analysis in this study used a simple linear regression test and an independent t-test test. The results of the study showed that there was a significant effectiveness of the word square learning model in improving the Indonesian vocabulary ability of third-grade students at MIN 2 Metro Pusat in the 2025/2026 academic year.